Parathyroid carcinoma presenting with pathologic fracture: Case report and review of the literature. Issue 11 (26th June 2015) - Fortson, James K.; Su, Roger; Patel, Vijaykumar G.; Lawrence, Gillian E.; Andersen, Peter
Abstract Background Parathyroid carcinoma is a rare neoplasm representing <1% of primary hyperparathyroidism cases. It is often not diagnosed until surgical exploration as a preoperative diagnosis is often not possible. Thus, preoperative staging for most patients is not feasible and this may compromise the treatment strategy. Methods and Results We report a case of a 29‐year‐old man presenting with avulsion fracture of the right elbow after a trivial fall. Neck exploration revealed an enlarged left lobe focally adherent to the larynx and trachea. Final pathology revealed parathyroid carcinoma with focally positive margin at the site of tracheal invasion. Conclusion Parathyroid carcinoma is a rare cause of primary hyperparathyroidism. The etiology of parathyroid carcinoma is usually obscured, and the initial operation offers the best chance for cure. © 2015 Wiley Periodicals, Inc. Head Neck 37: E139–E141, 2015